Beef value chain situation analysis for Uganda - Mubiru, Sarah; Marshall, Karen; Lukuyu, Ben A.; Oba, Peter; Ahumuza, Ronnie; Ouma, Emily A. (ILRI, 2023)
Beef is a major source of animal protein across the globe and its consumptions increases annually. Globally beef consumption is expected to reach 72 million t by 2025 from 70 million t in 2021 (OECD–FAO 2021). In Africa annual beef production was over 45 million kgs in each of 26 countries (FAOSTAT). In Uganda beef production had highest growth rate of 6.5% between 2001 and 2010 (FAOSTAT) and in 2018 was estimated at 217 million kgs (UBoS 2018). For the past 50 years, beef consumption in Uganda has been growing at a rate of 2%. The growth of the sector presents opportunities that can be harnessed for economic growth, increased revenue, employment and improved livelihoods. However, development of interventions for harnessing economic growth requires an in depth understanding of the sector and the value chain dynamics therein. To this end, ILRI commissioned a situational analysis of Uganda’s beef sector to provide relevant information for decision-making. The study relied on secondary information, databases and some key informant interviews. Information was obtained for all the segments of the beef value chain and its enablers. Information on quantities, quality, systems, costs, prices, markets, seasonality, challenges, opportunities and projections was obtained and synthesized; ultimately, potential intervention areas were identified.